PENGARUH KEPEMIMPINAN, MOTIVASI, DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN - Santoso, Wawa; Az Zahra, Fatimah (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to examine the effect of variables of leadership, motivation, and organizational commitment on employee performance of PT. Z. The sampling technique used on this research is purposive sampling with a total of 97 employees. Data was collected by spreading questionnaires. The data analysis method used is multiple linear regression analysis. The study result indicates that the variables of leadership and motivation affects the performance of employees, However organizational commitment does not affect the performance of employees.